Contaminação do lençol freático por hidrocarbonetos na região de Avaré - SP - Fogaça, Paulo Henrique de Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The contamination of water and soil is frequently caused by leakage and fuel can be prevented. Many incidents that contaminate the environmnent have occurred due to oil exploration and refining, as well as transport and storage of derivatives. As a result, the water table is reached by hazardous substances because they in most cases, carcinogenic, and depressants of the central nervous system. With CONAMA Resolution 273, from 2000, the water and soil of the regions where they are located fueling stations are now analyzed. Proven contamination, these sites have undergone a physical restructuring to adapt the storage tanks and service structure. In addition, the stations have the obligation to implement and effective remediation system, capable of making, again, water and soil appropriate to the services and the hman being without danger to health. This paper presents a study of soil contamination and remediation process and groundwater Avare region (SP) caused by gas stations and fuel supply in the region. Two different structures storage facilities were studied: buried tanks (Rank 1) and air tanks (Rank 2), and the data shown are from the reports prepared by CETESB on detailed investigation and remediation of these posts. Several analyzed of the soil and water were carried out by specialized companies, as well as monitoring and remediation of these. The main results show, for example, in relation to the first station, the quality of the local aquifer water found to be inadequate for eventual ingestion at thigh levels of concentration of benzene and toluene. After the remediation process, noted a reduction of concentrations of the chemical compounds of interest. The table near the station 2 also showed contamination due to diesel oil leaks. In this case, after the last period of analysis of the remediation process, there was a 100% effectiveness in remediation process

A contaminação de água e do solo é, muitas vezes, causada por derrame de combustíveis e pode ser evitada. Muitos incidentes que contaminam o meio ambiente têm ocorrido devido à exploração e refinamento de petróleo, bem como transporte e armazenamento de seus derivados. Como consequência, o lençol freático é atingido por substâncias perigosas por serem em grande parte dos casos, carcinogênicas e depressoras do sistema nervoso central. Com a Resolução CONAMA 273, a partir de 2000, a água e solo das regiões onde se localizam postos de armazenamento de combustíveis passaram a ser analisadas. Comprovada a contaminação, esses locais passaram por uma reestruturação física para adequação dos tanques de armazenamento e estrutura de atendimento. Além disso, os postos têm à obrigatoriedade de implantar um sistema de remediação eficaz, capaz de tomar, novamente, a água e solo adequados aos serviços e ao ser humano sem perigo à saúde. Este trabalho apresenta um estudo do processo de contaminação e remediação do solo e água subterrânea da região de Avaré (SP) causada por postos revendedores e de abastecimento de combustível da região. Foram estudados dois postos de armazenamento de estruturas diferentes: tanques enterrados (Posto 1) e tanques aéreos (Posto 2), e os dados apresentados foram retirados dos relatórios elaborados pelas firmas sobre a investigação detalhada e remediação dos referidos postos. Diversas análises do solo e da água foram realizadas por empresas especializadas, bem como o monitoramento e a remediação destes. Os principais resultados mostram, por exemplo, que em relação ao posto 1, a qualidade da águas do aquífero local encontrava-se inadequada para eventual ingestão com altos valores da concentração de Benzeno e de Tolueno. Após o processo de remediação, notou-se redução das concentrações dos Compostos Químicos de Interesse. O lençol freático próximo ao posto 2...
Keywords: Combustiveis; Tanques; Poluição; Meio ambiente - São Paulo (Estado); Agua potavel - Contaminação; Fuel